Reform of Human Trafficking Victim Protection Policy in Indonesia: A Human Rights and Restorative Justice Perspective - Fero Sanjaya; Herlita Eryke (PALAR | PAKUAN LAW REVIEW, 2026)
Purpose of this paper is to examine the legal framework of victim protection in human trafficking cases in Indonesia, which currently faces significant challenges regarding the fulfillment of victims' rights to restitution. Despite the existence of Law No. 21 of 2007, victims often encounter systemic barriers in obtaining recovery, leading to secondary victimization. Methods used in this study follow a normative legal research approach with statutory, conceptual, and case perspectives, specifically analyzing Supreme Court Decision No. 2355 K/Pid.Sus/2022. Research results indicate that the current restitution mechanism is merely decorative and highly dependent on the perpetrator's financial capacity, which is often non existent or hidden. The study finds a significant legal gap where the state lacks a mandatory safety net for victims when perpetrators fail to pay. Analysis reveals that the protection policy is still heavily "offender-oriented" rather than "victim-centered." The lack of synchronization between human trafficking laws and witness/victim protection regulations creates procedural fragmentation that hinders the restorative justice process. To address these issues, this paper argues for a legal reformulation that positions the state as the ultimate guarantor of victim recovery. Recommendationsinclude the urgent revision of the Human Trafficking Law to institutionalize a "Victim Recovery Fund" and the implementation of an Integrated Standard Operating Procedure (SOP) to ensure that legal, psychological, and financial recovery are handled simultaneously through a coordinated inter-agency system.